Digging the diversity of Iberian bait worms Marphysa (Annelida, Eunicidae) - Martin, Daniel (2020)
During a visit to polychaete-rearing facilities in the vicinity of Bay of Cádiz (SW Iberian Peninsula, Atlantic Ocean), we sampled two populations of Marphysa (Annelida, Eunicidae) originally occurring at nearby intertidal soft bottoms, one being more than twice as long as the other at the same age. We analysed them using partial sequences of two mitochondrial genes, 16S rDNA and Cytochrome Oxidase I, and classical morphological observations. Our molecular results confirmed that the two populations corresponded to two different species, with PTP species delimitation values ranging from 0.973 (long-bodied species) to 0.999 (short-bodied species). Morphologically, the short-bodied species resembles the recently redescribed M. sanguinea (Montagu, 1813), but differs mainly in having some parapodia with two subacicular hooks (one bidentate and one unidentate) and three types of pectinate chaetae, Two isodont present all along the body, and one particularly large anodont asymmetric appearing only from mid-posterior parapodia. The long-bodied species resembles Marphysa aegypti Elgetany, El-Ghobashy, Ghoneim and Struck, 2018 both in size and in having very robust, unidentate subacicular hooks (single in most parapodia, two-both similar in size and form-in some posterior parapodia), but differs, among other features, in the maxillary formula, the number of acicula per parapodia and the number and shape of pectinate chaetae. Accordingly, we are here fully illustrating and formally describing the two Iberian populations as Marphysa gaditana sp. nov. (short-bodied) and Marphysa chirigota sp. nov. (long-bodied) and we are emending the description of M. aegypti based on our revision of the type material. Also, we discuss on the distribution of the species of the sanguinea-group and on the relevancy of taxonomically robust studies when dealing with species of commercial interest having the potential of being globally spread through human activities, as well as on the misunderstandings caused by the incorrect use of the "cosmopolitan species" concept.